Suriname : 2003 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Suriname. (IMF Staff Country Reports; Country Report ;, 2003)
Suriname's mining-based economy has suffered from poor macroeconomic management. Executive Directors commended the authorities' efforts to stabilize the economic, fiscal, and monetary policies stances, and emphasized the need to accelerate structural reforms. They stressed the need for fiscal consolidation, exchange rate unification, economic diversification, and improvements in governance and tax administration. They welcomed the authorities' decision to subscribe to the General Data Dissemination System, and encouraged them to continue to take full advantage of the technical assistance being provided by the IMF and the Inter-American Development Bank.